RANCANG BANGUN APLIKASI SISTEM INFORMASI SEMINAR PRAKTISI POLBENG BERBASIS WEB MENGGUNAKAN METODE EXTREME PROGRAMMING - supendi, supendi; Jamaris, Muhamad; Nurjayadi, Nurjayadi; Karpen, Karpen (Jurnal Inovtek Polbeng Seri Informatika, 2024)
A practitioner seminar is an event where professionals in a specific field share their experiences and skills. The implementation of the Extreme Programming method in creating an Information System for Practitioner Seminars at Politeknik Negeri Bengkalis can be done effectively. Currently, the management of seminar data at Politeknik Negeri Bengkalis is still manual, including participant registration, attendance, and certificates. The current system results in poor data storage and the manual one-by-one distribution of seminar certificates to participants. This research aims to design and develop a system that will facilitate the management of seminar participant data. The system applied in this research is titled "Design and Development of a Web-Based Information System for Practitioner Seminars at Polbeng Using the Extreme Programming Method." The author hopes that this system will help manage practitioner seminar data efficiently and simplify data retrieval when needed. This system includes features such as participant data management, seminar registration, event scheduling, and participant certificates.